Goreckïs creative journeys between nature and culture. Around the ‘Copernicari Symphony - Małecka, Teresa (Interdisciplinary Studies in Musicology, 2018)
Henryk M. Gôrecki’s oeuvre is characteristic in its almost constant oscillation between meditation on the world, the universe, nature, and implication in history, tradition, culture; between the delight in the beauty of nature and the delight in culture. ‘We were no longer the centre of the universe, we became nothing.’This idea of the composer was fundamental for his creation of his II Symphony. Its two-movement form was a consequence of his own understanding of the Copernican revolution. Its Latin text was derived from the Book of Psalms; due to the circumstances of its commission, it also includes a fragment from Copernicus tractate. The distribution of tension in the first movement is non-trivial. Judging by the composer’s “cosmic” fascinations, the beginning is a “Big Bang”. The central climax of this movement appears in its finale, when the huge chorus sings and cries the words of the Psalms. In Movement Two we are ushered into a different, a lyrical world of contemplation. The soloists are singing in traditional and simplest possible way. The chorus, harmonized modally is singing the words of Nicolaus Copernicus about the “heaven” - “beauty” relation. Chorale-like, they place us in a transcendental dimension. The work is crowned with long-standing yet pulsating sonorities of the orchestral mass in pentatonic interval structure, resolved into an A flat major triad: in the tradition of Baroque rhetoric, depicts emotions of stillness, of the calm of the night; in late Romanticism - the emotion of mild and solemn. Perhaps these sonorities of the orchestral mass in the finale - that is exactly the sound of the Universe as Górecki has been expressed?